PENGARUH MINAT BELAJAR, KECERDASAN INTELEKTUAL, DAN KECERDASAN EMOSIONAL TERHADAP HASIL BELAJAR MATA PELAJARAN EKONOMI PADA SISWA KELAS XI IPS DI SMA NEGERI 1 MINAS KABUPATEN SIAK - Putri Diyah Makarti Desi; Gusnardi '; Fenny Trisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study is based on research conducted in SMA Negeri 1 Minas Kab. Siak. The purpose of this study was to determine whether or not the effect (1) Interest in learning about learning outcomes of Economic Subject (2) Intellectual Intelligence on Learning Outcomes of Economic Subject (3) Emotional Intelligence on Learning Outcomes of Economic subject and (4) Interest in learning, intellectual intelligence, and Emotional intelligence on Learning Outcomes of Economic Subject at class XI IPS in SMA Negeri 1 Minas Siak. This research uses descriptive quantitative method with multiple linear regression approach. The population in this study were all students of class XI IPS majors listed in SMA Negeri 1 Minas Siak. With a sample of 60 students drawn by the method of probability or randomly with a simple random sampling method. The instrument used was using a questionnaire to gauge interest in learning, intellectual intelligence and emotional intelligence and the semester report card Value Odd for Economics student learning outcomes. The results of multiple regression calculation with Interest in Learning (X1), Intellectual Intelligence (X2), Emotional Intelligence (X3) and the results studied Economics (Y). can be obtained by the equation Y = 39.471 + 0.576 X1 + 0.690 X2 + 0.155 X3. Where the results of the research shows that X1, X2 and X3 Simultaneous effect on Y. The results showed Rsquare of 0,392, which means that the independent variables used in this study affect the dependent variable by 39.2% while sisahnya influenced by variables outside of this study. partially wholly independent variable significant effect on the dependent variable, with the value X1 sig 0.017 <0.05, X2 sig 0.001 <0.05 and X3 sig 0.019 <0.05.Keywords: Interest in Learning, Intellectual Intelligence, Emotional Intelligence,Learning Outcomes